Comparison of Rectal Misoprostol’s Effect When Used Before And After An Elective Cesarean Section On Post Cesarean Bleeding - خنسة رقية; لينا رمضان; لؤي حسن (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Cesarean deliveries are among the most common major surgical interventions among women. Nevertheless, cesarean deliveries can lead to serious fetal or maternal complications, including primary postpartum hemorrhage (PPH), which can be a fatal complication and is the most common cause of maternal mortality worldwide, leading to over 100 000 maternal deaths annually. Misoprostol, a synthetic prostaglandin E1 analog, is widely used in obstetrics for the prevention and control of blood loss. Previous reports have shown that misoprostol is effective in reducing blood loss during and after cesarean delivery, whether administered orally, intravenously, or rectally. However, the optimum time for administration of misoprostol to achieve maximum blood loss reduction has not been adequately addressed. Therefore, the aim of the present study was to compare the efficacy of preoperative and postoperative rectally administered misoprostol (400 µg) in blood loss reduction during elective cesarean delivery to determine the optimum time for drug administration. Materials and methods: A number of 180 women who were admitted to our hospital because of elective cesarean section entered this clinical trial. They were divided into two groups. Group 1 received 400-μg of rectal misoprostol before the cesarean section and group 2 received 400-μg of rectal misoprostol after the surgery, the primary outcome was blood loss after cesarean delivery, Secondary outcomes were use of additional uterotonic drugs, postoperative hemoglobin and hematocrit concentration, change in hemoglobin and hematocrit concentration, adverse effects, and fetal and maternal morbidity. Results: The mean estimated blood loss after cesarean delivery was significantly lower in group 1 than in group 2. Similarly, more patients in group 2 than in group 1 needed additional uterotonic drugs. The estimated postoperative hemoglobin and hematocrit levels were significantly lower in group 2 than in group 1 as was the change in hemoglobin and hematocrit levels. Conclusion: 400 μg rectally administered misoprostol given before surgery more effectively reduced blood loss during elective cesarean than did postoperative administration. Furthermore, the frequency of adverse events did not vary depending on the timing of misoprostol administration. Keywords: Cesarean delivery, rectal misoprostol, postpartum hemorrhage